The Effect of Messages Delivered Through Video Media on Knowledge, Attitudes, and Practices of Exclusive Breastfeeding Among Mothers in the Working Area of the Bantargebang Community Health Center in 2022 - Zarfiel Tafal; Yennie Ariestanti; sherlyayutionika (Jurnal Ragam Pengabdian, 2026)
Exclusive breastfeeding can reduce infant mortality due to infection by up to 88%. Mothers' knowledge and attitudes are related to exclusive breastfeeding practices, and videos can be an effective medium for improving mothers' knowledge, attitudes, and practices. This study aims to determine the effect of video-based messages on mothers' knowledge, attitudes, and practices related to exclusive breastfeeding, as well as the dominant factors that influence these practices. The study design was a quasi-experimental pretest-posttest design. The research subjects were mothers with infants aged 0-5 months in the working area of the Bantargebang Community Health Center. Data collection was conducted through questionnaires (pretest and posttest), interviews (preliminary study and assessment), observation of practices, and video screening intervention. Data analysis used paired sample t-tests and Wilcoxon tests. There was a significant increase in knowledge (p=0.000, paired sample t- test), attitude (p=0.001, Wilcoxon test), and practice (p=0.000, Wilcoxon test) in the intervention group. Attitude was identified as the dominant factor influencing exclusive breastfeeding practices. Video messages through video media effectively enhance mothers' knowledge, attitudes, and exclusive breastfeeding practices. Attitude emerged as the most influential factor on practice after controlling for knowledge.